PELAKSANAAN SISTEM PERLINDUNGAN KONSUMEN BAGI PENGGUNA JASA ANGKUTAN UMUM BUS TRANS METRO PEKANBARU (TMP) DI KOTA PEKANBARU TAHUN 2016 - Fadli Syahputra; Muchid " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Transjakarta bus service business entrepreneurs Pekanbaru (TMP) has not granted the rights of consumers as users of Trans Metro bus service Pekanbaru (TMP) in terms of security and safety because there is still an accident. Pekanbaru City Community as a user of Trans Metro Bus Service Pekanbaru (TMP) is not fully understand procedure and standard claimed in PT (Persero) Asuransi Jasa Raharja in case of accident. The formulation of the problem: how is the implementation of consumer protection system for public transportation service users of Trans Metro Bus Pekanbaru (TMP) in Pekanbaru City in 2016 ?. The purpose of this research: to know the implementation of consumer protection system for public transportation service user of Bus Trans Metro Pekanbaru (TMP) in Pekanbaru City 2016 in accordance with Law Number 8 Year 1999 About Consumer Protection. Primary data sources through interviews as well as secondary data sources. Data analysis technique is conducted by qualitative descriptive analysis. Transparent: book clauses already covered by insurance are included in the ticket, while the Trans Metro Pekanbaru (TMP) schedule every route is listed around Bus Trans Metro Pekanbaru bus stop, Trans Metro Pekanbaru bus (TMP) gives the opportunity to travel for free at the beginning of the operation of public transport Bus Trans Metro Pekanbaru (TMP) for 3 (three) months. Accountability: the guarantee given is to give free travel by public transportation Bus Trans Metro Pekanbaru (TMP) as much as 10 (ten) times, the user of Trans Metro Bus Service Pekanbaru (TMP) has been covered by insurance if accidents happen. Conditional: Bus Trans Metro Bus service business entrepreneurs Pekanbaru (TMP) give a report in writing the whole event to the Regional House of Representatives (DPRD) Pekanbaru City. Participative: Bus Trans Metro Pekanbaru (TMP) is in conformity with the standard of proper operation Equal rights: Bus Trans Metro Pekanbaru (TMP) provides seats reserved for disabled, elderly, and pregnant women. The balance of rights and obligations: consumer rights regarding comfort, security and safety are provided in the form of Air Conditioner (AC) usage, raise and lower using centralized mechanical door, conduct selection in recruitment of Trans Metro bus driver Pekanbaru involving traffic police and Dinas Transportation (DISHUB) Pekanbaru City through the Field of Traffic and Road Transport (LLAJ).Keywords: Consumer protection system, Service